Пути развития стилистики русского языка во 2-ой половине ХХ в. - КОЖИНА, МАРГАРИТА Н. (Stylistyka, 2021)
The article presents historical-analytical review of the linguostylistics development from the time of stylistics discussion in the journal "Voprosy Yazykoznaniya" (1954- 1955). The further development of the main proЫems, outlined during the discussion, such as the proЫems of the subject of stylistic researches, stylistic resources of the language, the correlation of the notions "style of language" and "style of speech", stylistic status of fiction and others are traced. Since the 2nd half of the l 960s, the Russian stylistics began to develop intensively , especially its functional branch and also the branches of historical stylistics, comparative stylistics and stylistics of text. Also the article considers the issues of extralinguistic factors of style, integrated interdisciplinary research methods and others.